2008
DOI: 10.1016/j.ddmec.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Modifying skin pigmentation – approaches through intrinsic biochemistry and exogenous agents

Abstract: Rates of skin cancer continue to increase despite the improved use of traditional sunscreens to minimize damage from ultraviolet radiation. The public perception of tanned skin as being healthy and desirable, combined with the rising demand for treatments to repair irregular skin pigmentation and the desire to increase or decrease constitutive skin pigmentation, arouses great interest pharmaceutically as well as cosmeceutically. This review discusses the intrinsic biochemistry of pigmentation, details mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 120 publications
1
73
0
Order By: Relevance
“…The most important drugs causing oral pigmentation include quinolones, antimalarial drugs and minocycline (used for treatment of acne). 5 Polycyclic amines such as nicotine and benzopyrenes, and free radicals caused by tobacco smoking can also stimulate melanin synthesis by melanocytes. Melanin bonds to these agents to prevent cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…The most important drugs causing oral pigmentation include quinolones, antimalarial drugs and minocycline (used for treatment of acne). 5 Polycyclic amines such as nicotine and benzopyrenes, and free radicals caused by tobacco smoking can also stimulate melanin synthesis by melanocytes. Melanin bonds to these agents to prevent cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…The α-MSH binds to MC1R on the melanocyte [41] to increase tyrosinase activity and eumelanin production; this action could lead to regulation of melanocytes, skin pigmentation, Nitric oxide production and release of other signalling molecules from melanocytes [41]. Moreover, Pichler et al reported that α-MSH levels were significantly lower in vitiligo patients compared to normal individuals [42].…”
Section: Anti-melanocortin 1 Receptor (Mc1r)mentioning
confidence: 99%
“…It is caused by various physical, chemical and pathogenic causes of which the overexposure to the Sun is the common cause. [1] Its frequency had increased in recent years due to depletion in ozone layer and increased exposure to Ultra Violet radiation. Though it is not harmful, it is a serious business from the view of cosmetics.…”
Section: Introductionmentioning
confidence: 99%